Bridging the Gap: Population, skills and labour market adjustment in WA - Dockery, Alfred Michael; Duncan, Alan; Mavisakalyan, Astghik; Twomey, Chris; Vu, Lili Loan (Bankwest Curtin Economics Centre, 2022)
The 16th report in Bankwest Curtin Economics Centre’s Focus on WA series tackles the contentious issue of skills shortages in Western Australia. The state appears to be perpetually plagued by skills shortages, with regular reports of skills and labour shortages impacting upon sectors from agriculture to major resource and construction projects, to the childcare and aged care sectors; and extending throughout regional and remote Western Australia.
Focus on Western Australia Report Series No. 16
Keywords: Government, law and policy; Labour market; Migration and settlement